Current status and trends in the diagnostics of AML and MDS. Issue 6 (November 2018) - Shumilov, Evgenii; Flach, Johanna; Kohlmann, Alexander; Banz, Yara; Bonadies, Nicolas; Fiedler, Martin; Pabst, Thomas; Bacher, Ulrike
Abstract: Diagnostics of acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) have recently been experiencing extensive modifications regarding the incorporation of next-generation sequencing (NGS) strategies into established diagnostic algorithms, classification and risk stratification systems, and minimal residual disease (MRD) detection. Considering the increasing arsenal of targeted therapies (e.g. FLT3 or IDH1/IDH2 inhibitors) for AML, timely and comprehensive molecular mutation screening has arrived in daily practice. Next-generation flow strategies allow for immunophenotypic minimal residual disease (MRD) monitoring with very high sensitivity. At the same time, standard diagnostic tools such as cytomorphology or conventional cytogenetics remain cornerstones for the diagnostic workup of myeloid malignancies. Herein, we summarize the most recent advances and new trends for the diagnostics of AML and MDS, discuss the difficulties, which accompany the integration of these new methods and their results into daily routine, and aim to define the role hemato-oncologists may play in this new diagnostic era.